2019
DOI: 10.1038/s41598-019-54745-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-proliferative neurogenesis in human periodontal ligament stem cells

Abstract: Understanding the sequence of events from undifferentiated stem cells to neuron is not only important for the basic knowledge of stem cell biology, but also for therapeutic applications. In this study we examined the sequence of biological events during neural differentiation of human periodontal ligament stem cells (hPDLSCs). Here, we show that hPDLSCs-derived neural-like cells display a sequence of morphologic development highly similar to those reported before in primary neuronal cultures derived from roden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 104 publications
(177 reference statements)
7
29
0
Order By: Relevance
“…First are structural appearances that included cytoskeletal proteins. The differentiated cells exhibited a neuronal shape which positively detected neural cytoskeletal proteins such as β-III tubulin and neurofilament [12,13,20] or neuronal cell-specific markers such as Nestin, CD133, glial fibrillary acid protein (GFAP), MAP-2, enolase, and synaptophysin [11,15,20,21]. Second are functional characteristics involving functional neuronal networks, intercellular communication [40,41], and intracellular signaling cascades [12,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First are structural appearances that included cytoskeletal proteins. The differentiated cells exhibited a neuronal shape which positively detected neural cytoskeletal proteins such as β-III tubulin and neurofilament [12,13,20] or neuronal cell-specific markers such as Nestin, CD133, glial fibrillary acid protein (GFAP), MAP-2, enolase, and synaptophysin [11,15,20,21]. Second are functional characteristics involving functional neuronal networks, intercellular communication [40,41], and intracellular signaling cascades [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…MSCs can be characterized by differentiation into at least 3 specialized lineages: adipocytes, osteocytes, and chondrocytes [8]. Moreover, neuronal cells can be generated from MSCs by administration of extrinsic factors in the neuronal induction medium as demonstrated in several MSCs-derived tissues, including the adipose tissue [9], bone marrow [10], umbilical cord [11], cord blood [12], periodontal ligament [13], and both deciduous and permanent teeth [14]. Therefore, MSCs are an efficient stem cell source for neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, structural appearances that included cytoskeletal proteins. The differentiated cells exhibited neuronal shaped which positively detected neural cytoskeletal proteins such as β-III tubulin, neuro lament (12,13,20) or neuronal cell speci c markers such as Nestin, CD133, glial brillary acid protein (GFAP), MAP-2, enolase, synaptophysin (11,15,20,21). Secondly, functional characteristics involving functional neuronal networks, intercellular communication (40,41), and intracellular signaling cascades (12,23).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study 24 , we showed that human periodontal ligament-derived stem cells (hPDLSCs) can directly differentiate into neuron-like cells without passing through any mitotic stages. When hPDLSCs were exposed to a neural induction medium, we found that they rapidly underwent a dramatic change in shape and size; they initially adopted highly irregular forms before gradually contracting into round cells (neurogenesis).…”
Section: Introductionmentioning
confidence: 99%